Antibiotic-loaded nanoparticles targeted to the site of infection enhance antibacterial efficacy. (February 2018) - Hussain, Sazid; Joo, Jinmyoung; Kang, Jinyoung; Kim, Byungji; Braun, Gary; She, Zhi-Gang; Kim, Dokyoung; Mann, Aman; Mölder, Tarmo; Teesalu, Tambet; Carnazza, Santina; Guglielmino, Salvatore; et al.
Abstract Bacterial resistance to antibiotics has made it necessary to resort to using antibacterial drugs that have considerable toxicities. Here, we show that conjugation of vancomycin-loaded nanoparticles with the cyclic 9-amino-acid peptide CARGGLKSC (CARG), identified via phage display onStaphylococcus aureus (S. aureus ) bacteria and through in vivo screening in mice withS. aureus -induced lung infections, increases the antibacterial activity of the nanoparticles inS. aureus -infected tissues and reduces the systemic dose needed, minimizing side effects. CARG binds specifically toS. aureus bacteria but notPseudomonas bacteria in vitro, selectively accumulates inS. aureus -infected lungs and skin of mice but not in non-infected tissue andPseudomonas -infected tissue, and significantly enhances the accumulation of intravenously injected vancomycin-loaded porous silicon nanoparticles bearing CARG inS. aureus -infected mouse lung tissue. The targeted nanoparticles more effectively suppress staphylococcal infections in vivo relative to equivalent doses of untargeted vancomycin nanoparticles or of free vancomycin. The therapeutic delivery of antibiotic-carrying nanoparticles bearing peptides targeting infected tissues may help combat difficult-to-treat infections. Nanoparticles carrying an antibiotic and conjugated with a peptide identified via phage display that binds specifically toStaphylococcus aureus effectively suppress staphylococcal infections in vivo.